Evaluating effectiveness of pre-parental education for university students using Kirkpatrick model - Lee, Sung Hee; Lee, Seung A (Edelweiss Applied Science and Technology, 2025)
Pre-parental education is designed to equip prospective parents with essential parenting skills. Korea recently introduced it alongside population education as part of a broader strategy to address declining birth rates. However, there remains a scarcity of comprehensive studies evaluating its effectiveness in influencing childbirth-related attitudes. The Kirkpatrick training evaluation model, which assesses training effectiveness across four stages—reaction, learning, behavior, and results—has been widely applied in educational assessments. This study aims to evaluate how university students' reactions (Level 1) and learning outcomes (Level 2) from pre-parental education impact their expected number of children (a behavioral outcome, Level 3) using the Kirkpatrick model. A 10-week pre-parental education program, Healthy Parenting Recipe, was implemented for university students at K University in D City, South Korea, during the second semester of 2024. A total of 67 students participated in the study, and evaluations were conducted up to Level 3. Data were analyzed using SPSS/PC Windows 29.0, employing descriptive statistics and ordinal logistic regression. Greater satisfaction with course content (Level 1: Reaction) was associated with higher expected number of children (B = .234, CI: .063–.405, p = .007). Increased parenting knowledge (Level 2: Learning) also correlated with a higher expected number of children (B = 2.818, CI: .130–5.505, p = .04). Additionally, students prioritizing maternal career continuity expected more children (B = .771, CI: .188–1.353, p = .01), whereas those prioritizing meeting infant needs expected fewer (B = –.556, CI: –1.110– –.003, p = .049). These findings indicate that the results from Levels 1 and 2 significantly influence behavioral outcomes (Level 3). This study validates the interconnections among evaluation levels proposed by the Kirkpatrick model. Furthermore, it confirms the model’s effectiveness as a comprehensive evaluation framework for pre-parental education among university students.